Screen-printed SnO2/CNT quasi-solid-state gel-electrolyte supercapacitor. (2nd November 2017) - Kuok, Fei-Hong; Liao, Chen-Yu; Chen, Chieh-Wen; Hao, Yu-Chuan; Yu, Ing-Song; Chen, Jian-Zhang
Abstract: This study investigates a quasi-solid-state gel-electrolyte supercapacitor fabricated with nanoporous SnO2 /CNT nanocomposite electrodes and a polyvinyl alcohol/sulfuric acid (PVA/H2 SO4 ) gel electrolyte. First, pastes containing SnO2 nanoparticles, CNTs, ethyl cellulose, and terpineol are screen-printed onto carbon cloth. A tube furnace is then used for calcining the SnO2 /CNT electrodes on carbon cloth. After furnace-calcination, the wettability of SnO2 /CNT significantly improved; furthermore, the XPS analysis shows that number of C–O bond and oxygen content significantly decrease after furnace-calcination owing to the burnout of the ethyl cellulose by the furnace calcination processes. The furnace-calcined SnO2 /CNT electrodes sandwich the PVA/H2 SO4 gel electrolyte to form a supercapacitor. The fabricated supercapacitor exhibits an areal capacitance of 5.61 mF cm −2 when flat and 5.68 mF cm −2 under bending with a bending radius ( R ) of 1.0 cm. After a 1000 cycle stability test, the capacitance retention rates of the supercapacitor are 96% and 97% when flat and under bending ( R = 1.0 cm), respectively.